The Systematic Review: The impact of minimally invasive techniques on the outcomes of inguinal hernia repair - Maria Grys; Marta Piotraszewska; Magdalena Bartold; Filip Kochański; Janina Pohrybieniuk; Karolina Wołk; Dominika Błonka; Jan Pietrzak; Aleksandra Jaskulska; Magda Skudzińska (Quality in Sport)
Background